A survey of registered pharmacological clinical trials on rare neurological diseases in children in 2010–2020 - Chang, Xuting; Zhang, Jie; Jiang, Yuwu; Shang, Meixia; Wu, Ye (Frontiers in Pediatrics, 2022)
Objective To clarify the current state of methodology of clinical trials for rare neurological diseases in children, and to provide a basis for the further optimization of the trial design. Methods Data of clinical trials for the rare neurological diseases with childhood onset (searched through https://rarediseases.info.nih.gov/diseases and www.Orpha.net) registered on the Clinicaltrils.gov from January 2010 to June 2020 was collected. Analysis on the methodology of the clinical trials were performed, focusing on initiator of the studies, multi or single research center, study design, sample size, and the endpoint using in the trial. Results A total of 162 clinical trials were included, covering only 7.3% (61/835) of rare neurological diseases in children. 101 (62.3%) were initiated by pharmaceutical companies, and 61 (37.7%) by investigators. Most (95.4%) of global multicenter studies were initiated by pharmaceutical companies, whereas most (70.0%) of single-center studies were initiated by investigators (χ2 = 61.635, P < 0.001). Of the 162 trials, 74 (45.7%) were open-label single-arm trials, 68 (42.0%) were randomized double-blind parallel controlled trials (RCT), 12 (7.4%) were randomized crossover trials. Most of RCTs (73.5%) and 54.1% of open-label single-arm trials were initiated by pharmaceutical companies. The proportion of RCTs in clinical trials for diseases with a prevalence of ≥1/10,000 (62.5%) was higher than that in diseases with prevalence ≤1/1,000,000 (12.0%) or 1/1,000,000~1/10,000 (43.1%) (χ2 = 14.790, P = 0.001). The median expected sample size of the studies was 34 (4–500). 132 (132/162, 81.5%) studies enrolled fewer than 100 cases. Diseases with a prevalence of ≥1/10,000 had significantly larger sample sizes than other prevalence classes (P < 0.001, P = 0.003). Conclusions There were few clinical trials targeting on treatment of rare neurological diseases in children. Trials on rare diseases used fewer participants, and high-quality randomized controlled trials were less common. It is necessary to conduct global multicenter recruitment and choose optimal study designs to improve the level of evidence in clinical trials on rare diseases.